Preaxial Polydactyly in an Elderly Woman. (31st August 2022) - Chhabra, Barkha; Charls, Richy; Faillace, John J.
Abstract : A 70-year-old woman born and raised in India presented with Wassel type IV preaxial polydactyly of the right thumb and difficulty performing daily activities. She elected for surgical reconstruction after postponing the procedure for many years due to cultural norms. Her postoperative course was unremarkable. At her 3-month follow-up, she was diagnosed with carpal tunnel syndrome and underwent open carpal tunnel release. Preaxial polydactyly repair is unusual in patients older than 25 years. Though the duplication is considered lucky in South Asia, indications for this case were arthritic pain, cosmesis, and function. This case report details a unique indication for polydactyly reconstruction, arthritic pain, which may benefit hand surgeons when discussing the literature on adult polydactyly with their patients.